Validation of Modifications to the Soleris®E. coli Method for Detection and Threshold Determination of Escherichia coli in Select Foods: Level 3 Modification to AOAC Performance Tested MethodSM 101101. (2nd October 2021) - Beck, Nancy; Le, Quynh-Nhi; Mozola, Mark; Roman, Brooke; Montei, Carolyn; Zhang, Lei; Biswas, Preetha; Donofrio, Robert
Abstract: Background: Soleris ® E. coli is an automated, growth-based method for detection and semi-quantitative determination of Escherichia coli in foods. The method can be used in dilute-to-specification (threshold) or presence/absence modes. Objective: The objective of the study was to validate four modifications to the method: (1) a change in the vial detection window plug composition from agar to agarose to improve plug consistency and robustness, (2) a change in pre-enrichment incubation time for presence/absence testing from 6 h to 18–24 h, (3) a change in vial incubation temperature from 44.5 to 43.5°C, and (4) incorporation of a simple direct-from-vial confirmation test as an alternative to traditional procedures. Methods: Elements of the study included inclusivity/exclusivity testing, matrix testing in comparison to the ISO 7251:2005 reference method, reagent stability/lot-to-lot consistency testing, and an independent laboratory study. Results: In inclusivity testing, all 55 Escherichia coli strains tested produced positive results. In exclusivity testing, 30 of 31 strains of other bacterial species produced negative results, the sole exception being a strain of Enterobacter cloacae . In internal and independent laboratory matrix testing of mozzarella cheese, condensed milk, pasteurized liquid egg, and frozen green beans, results showed no significant differences in performance of the Soleris and reference methods with two exceptions, one in which the Soleris method produced more positive results, and one in which the reference method produced more positive results. Conclusion: Performance characteristics of the modified Soleris E. coli method are consistent with those of the original validated method. Highlights: The Soleris E. coli method offers improvements in ease of use and reagent robustness.